HUBUNGAN PENGETAHUAN IBU DENGAN MOTORIK KASAR ANAK USIA 3-4 TAHUN DI KAMPUNG SUKA MAKMUR KECAMATAN WIH PESAM KABUPATEN BENER MERIAH - Lia Muslima (Jurnal Maternitas Kebidanan, 2022)
The quality of the child's future can be seen from the optimal development and growth of the child, so that from an early age. Every child has different motor skills and intelligence. Gross motor (gross motor) is an aspect related to movement and posture, which attracts attention, because it is easy to observe. Delay in gross motor development in children aged 3-4 years is recorded at 49% , due to the lack of knowledge of mothers about the growth and development of their children that occur in developing countries, including in Indonesia. So mothers must pay attention to the development of their children according to their age. The aim of the research is to find out the relationship between mother's knowledge and gross motor skills of children aged 3-4 years in Suka Makmur village, Wih Pesam district, Bener Meriah district. This type of research is Analytical with a Cross Sectional approach. The population in this study are all mothers who have children aged 3-4 years in Suka Makmur Village, Wih Pesam District, Bener Meriah Regency, totaling 37 people. Sampling in this study used Total Sampling. , data were collected and measured using a questionnaire. This research was conducted on November 17-21 2022, while the research results obtained that the majority of Mother's Knowledge About Gross Motoric Children Aged 3-4 Years who could answer Yes were 18 people (48.6%), the majority of children's learning motivation was in the Good category as many as 13 people (35.15), Enough category as many as 6 people (16.2%), and Less category as many as 18 people (48.7%), the majority of mother's knowledge/stimulation is in the Good category as many as 17 people (45.9%) , There are 3 people (8.2%) in the Enough category and 17 people in the Less category (45.9%), The majority of siblings in the Good category are 12 people (32.4%), the Enough category is 3 people (8, 25), and the Less category as many as 22 people (59.4%). Statistical test results using Chi-squared obtained PValue = 0.02 <0.05, and PValue = 0.01 <0.05 The conclusion of this study is that there is a significant relationship between the relationship between mother's knowledge and gross motor skills of children aged 3-4 Year. Suggestions for mothers are expected to increase their knowledge about gross motor skills for children aged 3-4 years so that their children's growth and development can be even better.